2015
DOI: 10.15570/actaapa.2015.5
|View full text |Cite
|
Sign up to set email alerts
|

Faun tail: a rare cutaneous sign of spinal dysraphism

Abstract: Faun tail is a triangle-shaped hypertrichosis of the lumbosacral region. It is a rare condition and it can be a cutaneous marker of underlying spinal cord anomaly. We report on a 17-year-old female patient with hypertrichosis on the lumbosacral area since birth that was later diagnosed with tethered cord in magnetic resonance imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 5 publications
0
4
1
Order By: Relevance
“…2 In our case, the dermoscopic features were studied, which is the first report of such features, to our knowledge. Acquired reticular genital melanosis is not common, 1 and the dermoscopic reticular pattern that we observed in the pigmented lesions is not typical of genital melanosis in males, unlike in women. In males, melanosis often affects the glans penis rather than the shaft, 3 and dermatoscopy usually shows a parallel pattern, 3,4…”
Section: S Kumarcontrasting
confidence: 70%
See 4 more Smart Citations
“…2 In our case, the dermoscopic features were studied, which is the first report of such features, to our knowledge. Acquired reticular genital melanosis is not common, 1 and the dermoscopic reticular pattern that we observed in the pigmented lesions is not typical of genital melanosis in males, unlike in women. In males, melanosis often affects the glans penis rather than the shaft, 3 and dermatoscopy usually shows a parallel pattern, 3,4…”
Section: S Kumarcontrasting
confidence: 70%
“…In 2010, Romero-Mat e et al 1 reported two cases of reticulate genital pigmentation associated with localized vitiligo in two men, aged 21 and 75 years. In 2013, Harmelin et al 2 reported three cases of acquired genital hyperpigmentation associated with achromic lesions in three males aged 23, 18 and 54 years, in which the reticulate pigmentation had been present for several years.…”
Section: S Kumarmentioning
confidence: 99%
See 3 more Smart Citations